Application of Internal Financial Statements in Budgetary User Management in Croatia - Vesna Vasicek; Verica Budimir; Mirjana Hladika (Economic Review: Journal of Economics and Business, 2011)
The subject of this paper is to investigate the level of use of the internal financial statements of budgetary users in their management process. The main objective of this paper is to determine the importance of internal financial statements prepared according to the specific requirements of managers in decision making and budgetary user management.Another goal of this paper is to assess the implications of using a wide range of accounting information on efficiency of budgetary users management, rational spending of public resources,providing quality public services and satisfaction of public needs. As the result of application of the modified accrual basis in government accounting in Croatia, the current system provides a limited range of information presented in external financial statements. Initial hypothesis of the paper is that the internal financial statements in the Croatian public sector are underdeveloped and insufficiently used in decision making and budgetary user management. By applying the survey method, this paper aims at investigating the current level of using external and internal financial statements in decision making and management of Croatian budgetary users.The results obtained from the survey show that managers of most budgetary users consider that in formation presented in external financial statements are generally sufficient for decision making and successful management. Furthermore, the research results indicate that public managers are only partially familiar with the cost accounting and management accounting instruments. The information offered in the internal financial statements are not exploited enough in the pricing of services, performance measurement and the performance monitoring of service provision.
Keywords: 330